Factors Influencing the Choice of Seblak Cuisine by Muslim Women in Surabaya Based on Consumer Behavior Theory - Sari, Indah Puspita (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Indonesia’s rich culinary diversity reflects the culture and creativity of its society; however, the emergence of food trends like seblak illustrates changing consumer preferences, especially among youth and Muslim women. The rapid growth of seblak stalls across regions and its popularity for spicy, halal flavors make it an intriguing phenomenon to study from a consumer behavior perspective. This research aims to understand the reasons why Muslim women in Surabaya choose seblak using a quantitative approach and semi-structured interviews. The findings show that the main factors are the delicious and spicy taste, affordable price, easy accessibility, and guaranteed halal status. Respondents also mention that seblak is chosen because it is easy to find nearby and is supported by social media trends. Despite awareness of potential negative health effects from over-consumption, most still see seblak as a practical and enjoyable snack. This study contributes to understanding the behavioral factors of Muslim consumers and enriches the discourse on Indonesia’s culinary heritage as a cultural identity.